(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
A key point for a good performance in sports is to be concentrated. The concentration is the ability to put the attention into what is relevant to the task, that is, to isolate relevant cues in the athletic environment that exert stimulus control over skilled athletic behavior. This study used a covered practice and self-talks to bring the athlete behavior under stimulus control appropriate of the run, to increase concentration and consequently the speed on 60 meters hurdles to five elite runners. The purpose of this study was to investigate the effects of a specific self-talk on speed performance. A multiple-baseline design across people was employed. Results have shown that four of five runners improved their speed performance on 60 meters hurdles after treatment. The results are discussed in terms of correspondence between verbal and nonverbal behavior, specifically, the effects of rules on motor performance.